2016
DOI: 10.1098/rspb.2015.2954
|View full text |Cite
|
Sign up to set email alerts
|

How social network structure affects decision-making inDrosophila melanogaster

Abstract: Animals use a number of different mechanisms to acquire crucial information. During social encounters, animals can pass information from one to another but, ideally, they would only use information that benefits survival and reproduction. Therefore, individuals need to be able to determine the value of the information they receive. One cue can come from the behaviour of other individuals that are already using the information. Using a previous extended dataset, we studied how individual decision-making is infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 46 publications
2
44
0
Order By: Relevance
“…We found that social distance, which represents the typical distance at which flies communicate, displays evidence of high phylogenetic signal according to Pagel’s λin males and females and Blomberg’s K in females (Table 2). According to our data, most species tend to interact within 1-3 body lengths, and this range of interaction distance has been reported and applied by other researchers [5, 13, 2830]. The distance at which flies socially interact is conserved within different clades of our tree, suggesting that closely related drosophilids evolved similar mechanisms for social communication (Figure 4).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…We found that social distance, which represents the typical distance at which flies communicate, displays evidence of high phylogenetic signal according to Pagel’s λin males and females and Blomberg’s K in females (Table 2). According to our data, most species tend to interact within 1-3 body lengths, and this range of interaction distance has been reported and applied by other researchers [5, 13, 2830]. The distance at which flies socially interact is conserved within different clades of our tree, suggesting that closely related drosophilids evolved similar mechanisms for social communication (Figure 4).…”
Section: Discussionsupporting
confidence: 82%
“…Thus, we argue that the ways in which drosophilids behave and the structures of their groups have evolved, at least in part, by pressures exerted by their environments. It has been shown that how individuals organize in groups can influence their fitness and health [35]. Thus, understanding the influences on social organization is imperative for recognizing that disrupting these influences can impact the survival of a species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…193,262 Flies in social groups exchange information through non-random interactions, using sensory modalities such as olfaction, 193 and touch 174 (reviewed in Reference 154). 193,262 Flies in social groups exchange information through non-random interactions, using sensory modalities such as olfaction, 193 and touch 174 (reviewed in Reference 154).…”
Section: Structure Of Social Interaction Networkmentioning
confidence: 99%
“…Social learning, social space (or distance), and probably sociability too, are the outcome of a complex exchange of information, taking place within social interaction networks. 193,262 Flies in social groups exchange information through non-random interactions, using sensory modalities such as olfaction, 193 and touch 174 (reviewed in Reference 154). The receipt and processing of these cues subsequently can impact where a fly settles in a group, where they lay their eggs, and whether they avoid particular odors.…”
Section: Structure Of Social Interaction Networkmentioning
confidence: 99%